2001
DOI: 10.1097/00007632-200102010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Sagittal Vertebral Alignment in Flexion Determined by Dynamic Radiographs of the Cervical Spine

Abstract: Qualitative changes from extension to flexion and quantitative values of intervertebral differences in flexion radiographs help define the normal flexibility of the cervical spine more accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…In the sitting posture, the subjects were asked to perform movements to look at different targets : their feet (flexion) and the ceiling (extension) [13]. The median sagittal ROM of the cervical spine in the sitting posture was 11 (tenth to ninetieth percentile, [9][10][11][12][13][14][15][16][17][18] in the healthy control subjects and 11 (tenth to ninetieth percentile, [9][10][11][12][13] in patients [13]. There was no statistical difference between the two groups [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the sitting posture, the subjects were asked to perform movements to look at different targets : their feet (flexion) and the ceiling (extension) [13]. The median sagittal ROM of the cervical spine in the sitting posture was 11 (tenth to ninetieth percentile, [9][10][11][12][13][14][15][16][17][18] in the healthy control subjects and 11 (tenth to ninetieth percentile, [9][10][11][12][13] in patients [13]. There was no statistical difference between the two groups [13].…”
Section: Discussionmentioning
confidence: 99%
“…There was no statistical difference between the two groups [13]. The median sagittal ROM of cervical spine in the walking episodes was 13 (tenth to ninetieth percentile, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] in the healthy control subjects and 9 (tenth to ninetieth percentile, 7-11 ) in the patients [13]. There was statistical difference between the two groups [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Other studies have also focused on intervertebral motion in asymptomatic individuals. [12][13][14][15][16][17][18] Dvorak et al examined flexion and extension lateral cervical spine films in 44 people. 12 They found a mean rotation of 21°and a mean translation of 3.6 mm at C4 -C5.…”
Section: Discussionmentioning
confidence: 99%
“…11 As a reference to help identify abnormal motion, many researchers have reported on motion in the asymptomatic, intact cervical spine in vivo, using a variety of measurement techniques. [12][13][14][15][16][17][18] More recently, Reitman et al documented cervical intervertebral motion in 140 asymptomatic subjects with a validated, computer-assisted measurement technology. 19 Using the same measurement technology, Brown et al compared intervertebral motion following posterior cervical ligamentous sectioning in intact cadavers to intervertebral motion reported in the asymptomatic population and found that intervertebral rotation or translation measurements from flexionextension radiographs were inadequate to consistently determine even extensive posterior injury.…”
mentioning
confidence: 99%